Synchronizing migration with birth: an exploration of migratory tactics in female moose - Näsén, Linnéa (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2015)
Migration and giving birth are crucial decisions for animals during their life cycle, which may have lasting consequences on their population demography and fitness. Migration can entail a variety of possible effects for an individual, such as access to high quality food and reduced risk for predation. The moose (Alces alces) in northern Sweden is partially migratory and moose females are known to give birth to one or two calves. The synchrony between time of calving and timing of migration has not been compared before, especially in terms of energy maximizing and time minimizing perspectives, which may provide vital cues for fitness benefits of migration. I investigated effect of timing of birth and individual life history on distance, timing, stopovers and duration of 190 individually marked female moose that have been tracked for multiple years in ten different areas in northern Sweden. The effects of the life history variables (area, age, body mass, litter size) were tested by using Generalized Linear Mixed Models (GLMMs), and ANOVAs together with Turkey’s HSD tests were used to explain variation in movement between females of different reproductive status. Females that gave birth during migration had the longest duration of spring migration and used the most stopovers than others. Females that gave birth before spring migration arrived later in the summer ranges than other female groups. However, those that gave birth after spring migration had the quickest spring migrations. Younger females migrated earlier in autumn than older females and females with twins migrated earlier during autumn than other female groups. Such timing adjustments between migration and reproduction demonstrate that the time minimizing versus energy maximizing behavioural trade-offs can exist within a species, where individuals make trade-offs depending upon their life history and life cycle events.